The Malay Diplomatic Register in Correspondence: The Case Study of Bilateral Relations between Indonesia and Brunei - Efri Yoni; Mezia Kemala Sari (Edumaspul: Jurnal Pendidikan, 2026)
This study examines the existence of Malay diplomatic register in official correspondence between Indonesia and Brunei Darussalam. Employing a qualitative approach and documentary analysis of 27 sets of First-Person Notes (1996-2008), this research identifies lexical, pronominal, and syntactic characteristics that distinguish diplomatic register from general Malay varieties. Findings reveal that Malay diplomatic register is characterized by strategic deployment of Bahasa Dalam—the Brunei royal register—encompassing hierarchical honorific systems and personal pronoun choices calibrated to recipient status. However, misapplications of royal-exclusive terms such as berkenan to non-royal officials were documented, potentially generating negative impressions and reducing communicative effectiveness. This study confirms that register competence requires deep pragmatic understanding rather than mere lexical proficiency. Practical implications include development of diplomatic training modules emphasizing register socialization and contribution to terminology standardization for the Brunei-Indonesia-Malaysia Language Council. This research provides empirical grounding for strengthening bilateral relations through accurate linguistic communication and mutual cultural respect.